Impact of local and systemic factors on the incidence of oral implant failures, up to abutment connection - Ghada Alsaadi, Marc Quirynen, (Blackwell Synergy, 2007)
Aim: The aim of this retrospective study was to assess the influence of systemic and local bone and intra-oral factors on the occurrence of early implant failures, i.e. up to the abutment connection. Material and Methods: The surgical records of 2004 consecutive patients from the total patient population who had been treated in the period 1982–2003 (with a total of 6946 Bra°nemark systems implants) at the Department of Periodontology of the Catholic University Leuven were evaluated. For each patient the medical history was carefully checked. Data collection and analysis mainly focused on endogenous factors such as hypertension, coagulation problems, osteoporosis, hypo-hyperthyroidy, chemotherapy, diabetes type I or II, Crohn’s disease, some local factors [e.g. bone quality and quantity, implant (length, diameter, location), type of edentulism, Periotests value at implant insertion, radiotherapy], smoking habits and breach of sterility during surgery. Results: A global failure rate of 3.6% was recorded. Osteoporosis, Crohn’s disease, smoking habits, implant (length, diameter and location) and vicinity with the natural dentition were all significantly associated with early implant failures (po0.05). Conclusion: The indication for the use of oral implants should sometimes be reconsidered when alternative prosthetic treatments are available in the presence of possibly interfering systemic or local factors.